REPRODUCIBILITY OF PHYSIOLOGICAL VARIABLES OF THE SIX-MINUTE WALK TEST IN HEALTHY STUDENTS - Patrícia Morgana Rentz Keil; Janaína Cristina Scalco; Renata Maba Gonçalves Wamosy; Camila Isabel Santos Schivinski (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To verify the reproducibility of the six-minute walk test (6MWT) performance and its physiological variables in healthy students. Methods: This is as prospective cross-sectional study. The sample consisted of healthy students aged 6-12 years old from public and private schools in the region of Florianópolis City, Santa Catarina State, (Southern Brazil). The medical state was considered according to the health records and scores on the International Study of Asthma and Allergies in Childhood (ISAAC) and the spirometric values of forced expiratory volume in the first second and forced vital capacity above 80% of what was predicted. Two 6MWTs were conducted with a 30-minute interval between them, following the recommendations from the American Thoracic Society. Physiologic variables were recorded using the portable telemetric gas analyzer K4b2 (Cosmed®, Italy). For analysis, the dyspnea index, the perception of effort and performance variables identified in both 6MWT were considered. Data distribution was verified with the Shapiro-Wilk test and statistical analysis included paired t-test or Wilcoxon test, and intraclass correlation coefficient (ICC). The significance level adopted was 5%. Results: A total of 22 students with a mean age of 10.2±1.5 years participated in the study. The covered distance and the variation of oxygen consumption reproducibility between the two 6MWTs presented ICC=0.76 and ICC=0.86, respectively. There was also similar behavior of the physiological variables when comparing the two tests (p=0.001), especially the minute volume (MV), the oxygen consumption (VO2), and the carbon dioxide production (VCO2). Conclusions: The 6MWT showed reproducible values, both in performance and physiological parameters, in the healthy students analyzed.